2011
DOI: 10.1109/tse.2010.59
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Studies of Pair Programming for CS/SE Teaching in Higher Education: A Systematic Literature Review

Abstract: OBJECTIVE-The objective of this paper is to present the current evidence relative to the effectiveness of pair programming (PP) as a pedagogical tool in higher education CS/SE courses. METHOD-We performed a systematic literature review (SLR) of empirical studies that investigated factors affecting the effectiveness of PP for CS/SE students and studies that measured the effectiveness of PP for CS/SE students. RESULTS-Seventy four (74) papers were used in our synthesis of evidence, and 14 compatibility factors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
172
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(182 citation statements)
references
References 49 publications
5
172
0
5
Order By: Relevance
“…So, teachers are always looking for effective teaching methods to enhance student motivation, problem solving and metacognitive skills in learning programming. Notably, there has been much research done on how to teach programming courses in interesting and effective ways to novices [14,18,19,20,21,22]. However, those proponents accepted that "formal lectures are not a useful way of teaching programming" [10,23].…”
Section: Introductionmentioning
confidence: 99%
“…So, teachers are always looking for effective teaching methods to enhance student motivation, problem solving and metacognitive skills in learning programming. Notably, there has been much research done on how to teach programming courses in interesting and effective ways to novices [14,18,19,20,21,22]. However, those proponents accepted that "formal lectures are not a useful way of teaching programming" [10,23].…”
Section: Introductionmentioning
confidence: 99%
“…Pair programming is a collaborative programming practice that has been studied often with computer science students and professional programmers (Nagappan et al, 2003;Salleh, Mendes, & Grundy, 2011;VanDeGrift, 2004;Woszczynski, Guthrie & Shade, 2005). Pair programming places participants in dyads, working in tandem at one computer to complete programming assignments.…”
Section: Introductionmentioning
confidence: 99%
“…A review of 73 pair programming studies identified several benefits of this practice, including technical productivity (time spent on the program), improved program/design quality, better academic performance, and greater perceived satisfaction (Salleh et al 2011). Pair programming improved retention within the CS major, which was defined as students who were more likely to pursue a higher level programming course and/or eventually to pursue a degree in CS (McDowell, Werner, Bullock, & Fernald, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Course completion rate: [12], [17], [23].  Improved personality [27], [28], [29], [35] Nearly, all of the research work was carried out in the domain of education and have used the students as subjects. The experiments were done using the laboratory course work.…”
mentioning
confidence: 99%